(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Language is an integral part of cultural identity. When a language becomes extinct (disappears), a vital aspect of a community’s heritage is lost. This loss can lead to a sense of disconnection, marginalisation and the erosion of intergenerational transmission of cultural values and knowledge. This has the tendency of posing serious danger to the cultural heritage, social cohesion and cognitive diversity of a given community and in the long-run, national development. Hence, there is need to ensure that languages spoken by people of different communities are maintained and preserved. This paper explores the issue of language extinct; the dangers associated with language extinction; the need for maintaining and preserving the indigenous languages by ensuring that languages are maintained; and the implication of language extinction on national development. It was therefore concluded that there is need for the indigenous languages to be maintained and preserved in order to avoid their being extinct and thus hinder national development. Some of the recommendations made are as follow: All indigenous languages should be properly documented; investment should be made on language revitalisation programmes by providing resources for language learning, teaching materials, and community engagement activities; Individuals should be sensitised of the importance of the indigenous languages; Public awareness should be raised through campaigns and the media to foster support for language maintenance and preservation efforts.